FAO/IBPGR technical guidelines for the safe movement of coconut germplasm - Frison, Emile A.; Putter, C.A.J.; Diekmann, M.; Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (1993)
Published with the support of Overseas Development Administration (ODA), UK